Optimizing hybrid with improved resistance to rice blast and superior ratooning ability - Liang, Yi; Yi, Zhaofeng; Zhuang, Wen; Peng, Teng; Xiao, Gui; Jin, Yunkai; Tang, Qiyuan; Xiong, Jiaojun; Deng, Qiyun; Zhou, Bo; Liu, Xionglun; Wu, Jun (Elsevier, 2025)
The ratooning system enhances agricultural efficiency by reducing secondary sowing and resource input while maintaining rice yield parity with double cropping. However, the prolonged growth duration of the rice ratooning system extends the exposure window to Magnaporthe oryzae infection, thereby elevating the probability of disease incidence. To address this, we employed molecular marker-assisted selection (MAS) to introduce the rice blast resistance gene Pikh into the paternal line Chuanghui 911 (R911) of the high-yielding ratoon rice variety Y Liangyou 911 (YLY911), generating two blast-resistant restorer lines (T002 and H66-3). Through hybridization of H66-3 with three male sterile lines, three hybrid combinations Y Liangyou H66-3 (YLYH66), Yangliangyou H66-3 (OLYH66), and Shuangliangyou H66-3 (SLYH66) were developed. Comprehensive evaluation of the agronomic traits revealed SLYH66 as the optimal combination, exhibiting robust ratooning ability, high total yield, and superior rice quality, including improved grain appearance and milling characteristics. This study advances germplasm innovation for disease-resistant ratoon rice and provides a strategic framework for breeding high-yielding, quality-focused varieties, bolstering the sustainable development of ratoon rice systems.